Reformer als Ketzer: Heterodoxe Bewegungen von Vorreformatoren - Frank, Günter; Niewöhner, Friedrich (frommann-holzboog Verlag, 2004)
The concept of a unity and a uniformity of the Christian religion (orbis christianus) in patristics and in the Middle Ages has proven to be an illusion. In fact since Christianity originated there has been a large number of heterodox movements, some of which could never be absorbed by the Christian church. Movements such as early Christian Gnosticism, the Paulicians, the Bogomils, the Antitrinitarians, the Cathars, the Albigensians and the Waldensians marked a religio-historical zone between Armenia and the Iberian Peninsula whose vitality endured for centuries. Based on examples, this volume provides an insight into the history of some of these movements summarized under the central concept of a so-called pre-Reformation, a term used up to the 19th century. Attention. The digital edition does NOT contain the article: Peter Dinzelbacher: Die Achsenzeit des Hohen Mittelalters und die Ketzergeschichte.